The Effect of Leadership Style, Communication and Work Motivation on Employee Performance During the Covid-19 Pandemic - Dede Hertina; Hikmat Agustian; Nadya Kirana (Politeknik APP Jakarta, 2024)
This study aimed to determine the effect of leadership style, communication, and motivation on employee performance during the Covid-19 pandemic. The population in this study is PT. XYZ, totaling 45 employees using purposive sampling, obtained a sample of 35 people. The research criteria are employees who work from home. The analytical methods used are the validity and reliability test, classical assumption test consisting of multicollinearity test, multiple regression analysis, and hypothesis testing through t and F tests. The results showed that leadership style, communication, and motivation significantly affected employee performance. While the study's results partially stated that communication had a significant effect on employee performance, the results indicated that leadership and work motivation had no effect on employee performance.